2014
DOI: 10.3136/fstr.20.711
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity of Ursolic Acid Isolated from Thymus vulgaris, L.

Abstract: Thymus vulgaris L. (Thyme)is an aromatic medicinal herb widely used in folk medicine, as a food seasoning and herbal tea, and as an essential oil. A 70% EtOH extract from the leaves of thyme was prepared and a component was purified and characterized using an in vitro bio-assay based on the inhibition of angiotensin I-converting enzyme (ACE). Ursolic acid (1), a known pentacyclic triterpene acid, was isolated from the leaves of thyme and its structure was characterized by 1 H, 13C-NMR and 2D NMR spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…Further research has been carried out in various directions. Vasorelaxant properties of ursolic acid were investigated by Aguirre-Crespo et al [130], Rios et al [131] and Shimada and Inagaki [132]. The first two teams connected the activity of UA with the production and release of nitric oxide (NO) in isolated thoracic aorta and in vivo on Wistar rats, respectively.…”
Section: Impact Of Ursolic Acid On Condition and Functioning Of Bomentioning
confidence: 99%
“…Further research has been carried out in various directions. Vasorelaxant properties of ursolic acid were investigated by Aguirre-Crespo et al [130], Rios et al [131] and Shimada and Inagaki [132]. The first two teams connected the activity of UA with the production and release of nitric oxide (NO) in isolated thoracic aorta and in vivo on Wistar rats, respectively.…”
Section: Impact Of Ursolic Acid On Condition and Functioning Of Bomentioning
confidence: 99%
“…It was discovered that UA reduced genetically hypertensive rat heart rates by 32%. Shimada and Inagaki 73,74 looked into UA's vasorelaxant properties, targeted at the inhibitory action of the angiotensin I‐converting enzyme, which is crucial for blood pressure regulation. Also, isoproterenol injection has been used to cause myocardial infarction artificially, whereas UA was being utilised as a molecule with potent inhibitory action.…”
Section: Therapeutic Potential Of Uamentioning
confidence: 99%
“…The potential effect of ursolic acid analogues on the heart had been demonstrated by several investigators. For instance, Somova, et al, (2003) showed ursolic acid to be able to lower the heart rate of genetically hypertensive rats by 32% and also ursolic acid had been shown to have protective effect on the cardiovascular systems ( [16], [17]) as well as inhibiting the activity of angiotensin converting enzymes [18]. Esculentoside (compound 4), an imidazole pyridine analogue showed positive inotropic and positive chronotropic effect on the animal.…”
Section: Cardiotonic Activities Of a Esculentus Fruit Extract And Its...mentioning
confidence: 99%